Consensus report: clinical recommendations for the prevention and management of the nocebo effect in biosimilar‐treated IBD patients. Issue 9 (1st April 2019) - Pouillon, Lieven; Danese, Silvio; Hart, Ailsa; Fiorino, Gionata; Argollo, Marjorie; Selmi, Carlo; Carlo‐Stella, Carmelo; Loeuille, Damien; Costanzo, Antonio; Lopez, Anthony; Vegni, Elena; Radice, Simona; et al.
Summary: Background: The nocebo effect is a negative effect of a pharmacological or nonpharmacological medical treatment that is induced by patients' expectations, and that is unrelated to the physiological action of the treatment. The nocebo effect can negatively affect treatment outcomes. Aim: To develop evidence‐based consensus recommendations for the prevention and management of the nocebo effect in biosimilar‐treated patients with IBD. Methods: The "NOCE‐BIO Consensus Group" was composed of 19 members from five European countries, and with different fields of expertise. A literature review on the nocebo effect, with specific focus on information about its prevention and management in biosimilar‐treated IBD patients, was performed. Preliminary statements were formulated and voted on during a consensus group meeting held in Milan, Italy, in July 2018. A statement was accepted if >75% of participants voted 4 ("agree") or 5 ("strongly agree") on a scale of 1‐5. Results: Consensus was reached on 11 recommendation statements. Seven statements reached consensus after one voting round and four statements reached consensus after two voting rounds. All statements were supported by very low‐quality level of evidence. The panel agreed that patient‐health‐care provider relationship is a key driver of acceptance of biosimilars, which limits the risk of negative bias and the nocebo effect. Lack of knowledge among patients and health‐care providers about the effectiveness and safety of biosimilars should be minimized. Education about biosimilars needs to be tailored to the individual patient, and positive framing is recommended. Conclusions: The nocebo effect is under‐recognised in the era of biosimilars, although it may negatively impact on the cost‐savings of biosimilars. Future research should focus on the magnitude, the risk factors, the impact, and the management of the nocebo effect in biosimilars‐treated IBD patients.